Use of Coconut Oil Massage versus Olive Oil Massage on Selected Physical and Physiological Parameters among Low Birth Weight Newborns in Selected Hospitals, in West Bengal - Dipa Ghosh; Smritikana Mani; Parul Datta (GLOBAL HEALTH SCIENCE GROUP, 2020)
The most significant contributing factor of neonatal mortality and morbidity is low birth weight (LBW). Oil massage helps in growth and development in LBW infants. The purpose of the study is to evaluate the effectiveness of coconut oil versus olive oil massage on selected physical and physiological parameters among LBW newborns. Ethical permission was taken. The study design is quasi experimental time series design. 30 LBW newborns (10 in coconut, 10 in olive & 10 in control group) were selected by non-probability purposive sampling. Data were collected from NICU by using valid and reliable Record Analysis, Physical Assessment, Modified Brazelton’s Scale and Maturity Assessment Scale. 10 ml /kg/day oil applied once only for 15 minutes upto 28th day. Weight, length, head and chest circumference, sleep, cry and maturity were assessed on 8th, 15th, 22nd and 29th day for each newborn. The result showed that there were no significant difference in physical parameters on 29th day of observation among three groups except weight gain (F=8.70, p=0.001207). There were significant difference in all post assessments of sleep. There were significant difference in cry score on 15th day (p=0.007701) and 22nd day (p=0.000758) of observation. Statistically significant differences were not found in all assessment of maturity. It can be concluded that oil massage has positive effect, compared to control. The study has a great implication in nursing service by practicing oil massage helps to gain weight and improve behaviour among LBW newborns. A similar study could be conducted using large sample for generalization.